Current Controversies and Solutions Related to Adoption in Georgia - Kukhianidze Ketevan (European Scientific Journal, ESJ, 2017)
Adoption in Georgia is a matter of Family Law. The institute, in its essence, has always been one of the most sensitive matters which was getting more and more actual as the centuries passed and is still faced as one of the most important issues of the modern era, which needs a new approach and deep analysis. This article aims to review the current issues related to the adoption and suggest the recommendations on improvement of the institute.